Radiotherapy plus CAR-T cell therapy to date: A note for cautions optimism? - Huan, Tian; Li, Hongbo; Tang, Bin (Frontiers in Immunology, 2022)
Radiotherapy (RT) is a traditional therapeutic regime that focuses on ionizing radiation, however, RT maintains largely palliative due to radioresistance. Factors such as hypoxia, the radiosensitivity of immune cells, and cancer stem cells (CSCs) all come into play in influencing the significant impact of radioresistance in the irradiated tumor microenvironment (TME). Due to the substantial advances in the treatment of malignant tumors, a promising approach is the genetically modified T cells with chimeric antigen receptors (CARs) to eliminate solid tumors. Moreover, CAR-T cells targeting CSC-related markers would eliminate radioresistant solid tumors. But solid tumors that support an immune deserted TME, are described as immunosuppressive and typically fail to respond to CAR-T cell therapy. And RT could overcome these immunosuppressive features; thus, growing evidence supports the combination of RT with CAR-T cell therapy. In this review, we provide a deep insight into the radioresistance mechanisms, advances, and barriers of CAR-T cells in response to solid tumors within TME. Therefore, we focus on how the combination strategy can be used to eliminate these barriers. Finally, we show the challenges of this therapeutic partnership.